Modeling Lane-Keeping Behavior of Bicyclists Using Survival Analysis Approach. (17th February 2013) - Guo, Hongwei; Wang, Wuhong; Guo, Weiwei; Zhao, Facheng
Abstract : Bicyclists may cross the bicycle lane and occupy the adjacent motor lanes for some reason. The mixed traffic consisting of cars and bicycles shows very complicated dynamitic patterns and higher accident risk. To investigate the reason behind such phenomenon, the lifetime analysis method is adopted to examine the observed data for the behavior that bicycles cross the bicycle lane and occupy the adjacent motor lanes. The concepts named valid volume and probability of lane-keeping behavior are introduced to evaluate the influence of various external factors such as lane width and curb parking, and a semiparametric method is used to estimate the model with censored data. Six variables are used to accommodate the effects of traffic conditions. After the model estimation, the effects of the selected variables on the lane-keeping behavior are discussed. The results are expected to give a better understanding of the bicyclist behavior.